ANAMMOX: SUATU PROSES BARU DALAM DAUR NITROGEN YANG MENAWARKAN BANYAK PELUANG DALAM PENGELOLAAN PENCEMARAN AIR AKIBAT NITROGEN - Samekto, Riyo (Innofarm:Jurnal Inovasi Pertanian, 2009)
ABSTRACTS The paper is to study the anammox (anaerob ammonium oxydation) and its chances to be used in waste water treatments. The nitrogen cycle has been developing in 15 years recently from without anammox and OLAND processes to with of them. The characteristics of anammox microorganisme, its biodiversity, its cell biology, and its growth, have been studied beside of explanation of biochemistry of anammox. The methods to investigate are also conducted by 15NH4+/ 15NO3-, lipids analysis (ladderane lipids), fluorescence in situ hybridization (FISH), and phylogenic analysis of partial 16 rRNA gene. All of them will increase the knowledge of waste water treatments. SHARON and ANAMMOX technigues are example of the efficient use system in waste water treatments being used lately. Key words : anammox, waste water treatment.